Modeling of competitive interactions: basic regularities. Part 1 - S. Yu. Malkov (Russian Journal of Economics and Law)
Objective: to analyze the general patterns of socio-economic and political dynamics (both within society and in interstate relations) caused by the presence of competition between key economic and political actors.Methods: methods of mathematical dynamic modeling were used to study competitive interactions.Results: the attitude to competition as a social phenomenon is ambiguous. It is considered either as a positive (for example, in market economy studies), or as a negative (for example, when considering interstate conﬂicts) factor. The paper attempts to analyze the general features of competitive interactions based on the study of the basic mathematical model describing competition in socio-economic and socio-political spheres. Using the basic mathematical model, various regimes of competitive interactions are considered; the conditions for the transition from one regime to another are determined; examples of the implementation of these modes in the economy are given.Scientiﬁc novelty: in the course of the research using mathematical modeling, the main attention was paid to the so-called non-robust (according to A. A. Andronov) cases of the implementation of competitive interaction, which have rarely been considered in the scientiﬁc literature so far, but are often found in real life.Practical signiﬁcance: the results of analysis and mathematical modeling allow establishing the conditions under which competition stimulation contributes to economic development and under which it leads to crisis situations.